Optimal rescheduling of generators for congestion management and benefit maximization in a decentralized bilateral multi-transactions power network - Singh B.; Mahanty R.; Singh S.P. (My University, 2025)
This paper presents a framework to achieve an optimal power flow solution in a decentralized bilateral multitransaction- based market. An independent optimal dispatch solution has been used for each market. The interior point (IP)-based optimization technique has been used for finding a global economic optimal solution of the whole system. In this method, all the participants try to maximize their own profits with the help of system information announced by the operator. In the present work, a parallel algorithm has been used to find out a global optimum solution in decentralized market model. The study has been carried out on a modified IEEE-30 bus system. The results show that the suggested decentralized approach can provide a better optimal solution. The obtained results show the effectiveness of IP optimization-based optimal generator schedule and congestion management in the decentralized market.